Examining Relationship between Autonomous Agent and Desirable Government in Kant's Thought - meysam jafari; Amir Masood Shahramnia (رهیافتهای سیاسی و بین المللی)
Freedom is the most important concept in Kant's practical philosophy. Purpose of this paper is to examine relation between freedom and other concepts of Kant's practical philosophy with politics in general and desirable government in particular. We first provided a theoretical framework derived from phenomenology theory. We studied it in a descriptive-analytical method. In this theoretical framework, we can analyze how to prove the freedom of human will. The authority is base of Kant's practical philosophy and the two concepts of "duty" and "right" are determined by it. Duty in realm of inner freedom is object of ethic and right in realm of external freedom is object of private and public rights. By examining Kant's political thought a number of important results were obtained; first, when one's practice is ethically valid that be completely free and there is no other motive other than free will (principle of duty). Under these circumstances, individual’s perfection is possible. The characteristics of a Kant's desirable government that provide the conditions for individual’s perfection are: 1- Ending human beings 2- Individual freedom 3- Rule of law 4- Principle of separation of powers. Kant introduces the constitutional republic as the desirable state.